Analysis of Swearing in the Novel《活着 Huózhe》 By 余华 Yu Hua - Tsabita Tuffahati (Green Publisher Indonesia, 2025)
Swearing represents a significant yet underexplored aspect of Chinese literary discourse, particularly in contemporary novels that reflect social realities and cultural transformations. This linguistic phenomenon becomes especially prominent in literature depicting periods of social upheaval, where characters express intense emotions through various forms of profane language. This study examines the types, forms, and functions of cursing contained in the novel entitled 《活着 Huózhe》 by Yu Hua (1992). The purpose of this study was to analyze cursing based on the types and forms of cursing according to the theory of Wijana (2004). Then, in classifying curse words based on the function of cursing, the researcher refers to the theory of Andersson and Trudgill (1990) and the theory of Shi Wei and Luo Xiao Nan (2009). This study uses a qualitative descriptive analysis method with a structural textual approach and documentation techniques. The results showed: first, the types of swearing in this novel consist of five categories, namely circumstances, animals, objects, body parts, kinship, and professions; second, there are three kinds of swear words: words, phrases, and clauses; third, there are six kinds of swearing functions, namely expletive/emotional, abusive/warning, humor, auxiliary, attitude, and social. This study contributes to both Chinese linguistics and literary criticism by providing empirical evidence for the systematic use of profane language in contemporary Chinese fiction, offering insights for language educators, translators, and scholars of Chinese literature and culture.